Valproic acid Suppresses Breast Cancer Cell Growth Through Triggering Pyruvate Kinase M2 Isoform Mediated Warburg Effect. (13th July 2021) - Li, Zhen; Yang, Lina; Zhang, Shuai; Song, Jiaqi; Sun, Huanran; Shan, Changliang; Wang, Dan; Liu, Shuangping
Energy metabolism programming is a hallmark of cancer, and serves as a potent target of cancer therapy. Valproic acid (VPA), a broad Class I histone deacetylases (HDACs) inhibitor, has been used as a therapeutic agent for cancer. However, the detail mechanism about the potential role of VPA on the Warburg effect in breast cancer remains unclear. In this study, we highlight that VPA significantly attenuates the Warburg effect by decreasing the expression of pyruvate kinase M2 isoform (PKM2), leading to inhibited cell proliferation and reduced colony formation in breast cancer MCF-7 and MDA-MB-231 cells. Mechanistically, Warburg effect suppression triggered by VPA was mediated by inactivation of ERK1/2 phosphorylation through reduced HDAC1 expression, resulting in suppressing breast cancer growth. In summary, we uncover a novel mechanism of VPA in regulating the Warburg effect which is essential for developing the effective approach in breast cancer therapy.